What Are the Effects of a Mediterranean Diet on Allergies and Asthma in Children? - Castro-Rodriguez, Jose A.; Garcia-Marcos, Luis (Frontiers in Pediatrics, 2017)
This review updates the relationship between the adherence to Mediterranean diet ([MedDiet] assessed by questionnaire) and asthma, allergic rhinitis or atopic eczema in childhood. It deals with the effect of MedDiet in children on asthma/wheeze, allergic rhinitis and atopic dermatitis/eczema; and also with the effect of MedDiet consumption by the mother during pregnancy on the inception of asthma/wheeze and allergic diseases in the offspring. Adherence to MedDiet by children themselves seems to have a protective effect on asthma/wheezing symptoms after adjustment for confounders, although the effect is doubtful on lung function and bronchial hyperresponsiveness. In contrast, the vast majority of the studies showed no significant effect of MedDiet on preventing atopic eczema, rhinitis, or atopy. Finally, studies on adherence to MedDiet by the mother during pregnancy showed some protective effect on asthma/wheeze symptoms in the offspring only during the first year of life, but not afterwards. Very few studies have shown a protective effect on wheezing, current sneeze, and atopy; and none on eczema. Randomized control trials on the effect of the adherence to MedDiet to prevent (by maternal consumption during pregnancy) or improve (by child consumption) the clinical control of asthma/wheezing, allergic rhinitis or atopic dermatitis are needed.